Effects of exercise during pregnancy on postpartum depression: a meta-analysis - Wang, Yuanyuan; Pan, Mengtin; Wei, Baojian; Sun, Huiwen; Huang, Jing (Quality in Sport, 2025)
Background: Postpartum depression is a pervasive depressive episode in the postpartum period that adversely affects the mother, her partner, mother-infant interaction, and offspring development. There are many limitations in the treatment of postpartum depression, which makes prevention during pregnancy important. Exercise has many brain and psychological benefits, but current results are inconsistent as to whether exercise during pregnancy prevents postpartum depression. Objective: The goal of this meta-analysis was to systematically assess the effect of exercise during pregnancy on postpartum depression, to provide clinicians with the most up-to-date evidence, and to provide additional information to improve guidelines for the prevention of postpartum depression. MATERIALS AND METHODS: This study was conducted in accordance with the PRISMA systematic evaluation statement. Four electronic literature databases were searched: PubMed, Web of Science, Embase, and Cochrane Library.The search was conducted from the time of construction to March 2025. Data were analyzed using RevMan 5.4.1 and stata17. RESULTS: A total of six randomized controlled trials with 1787 pregnant women were included. Exercise interventions were in the form of aquatic exercise, home exercise and group exercise. Exercise intervention durations ranged from eight weeks to five months. The results of the meta-analysis showed that exercise during pregnancy reduced the severity of postpartum depression [MD=-1.54, 95% CI (-2.69, -0.39), P=0.009]. However, the small number of included studies and high heterogeneity suggest that this result should be treated with caution. Conclusion: Exercise during pregnancy reduces the severity of postpartum depression, but more high-quality randomized controlled trials are needed to obtain more accurate results in the future.